Misconceptions and Game Form Recognition: Challenges to Theories of Revealed Preference and Framing - Cason, Timothy N.; Plott, Charles R. (Journal of Political Economy, 2014)
This study explores the tension between the standard economic theory of preference and nonstandard theories of preference that are motivated by an underlying theory of framing. A simple experiment fails to measure a known preference. The divergence of the measured preference from the known preference reflects a mistake, arising from some subjects’ misconception of the game form. We conclude that choice data should not be granted an unqualified interpretation of preference revelation. Mistakes in choices obscured by a possible error at the foundation of the theory of framing can masquerade as having been produced by nonstandard preferences.